Dwie przestrzenie wojennej propagandy. Język utworów moskiewskich Okien TASS - Książek, Agata (Studia Rossica Posnaniensia, 2021)
The aim of the article is to analyze the language of the Soviet propaganda posters from the Second World War period, containing the poetic commentary of the members of the Moscow TASS Agency. The research reveals the main means of persuasion used in the poems. The subject of the analysis is the phenomenon of spreading ideas in two basic social spheres that occurred in the Soviet Union during the war period, which include people who took direct part in military actions, and Soviet citizens who provided the army with all the necessary materials. Texts addressed to potential soldiers contained a direct call to defend the homeland and family. Their most important manipulative tools were emotional arguments and the technique of stereotyping the enemy. Ideas and personal patterns were instilled in the minds of the fighters with various linguistic manipulation techniques. The propaganda referenced to the belongingness need. Different propaganda techniques were used in poems targeted at people behind the lines of hostilities. The authors of the texts of TASS Windows used colloquial language, comprehensible to a wide audience. They created a vision of a world divided into two opposite poles and referred to respected authorities or raised new role models. The propaganda of the victory also required different techniques of information manipulation. The TASS Windows present the unique contribution of the Soviet poets to the action of the mobilization of society to take part in the fight against the German aggressor.